Incidencias del teletrabajo en el clima organizacional en una empresa de medicina prepagada - Mejía García, Daniela Mayerlit (2024)
This research analyzes the impact of teleworking on the organizational climate within a prepaid medical company in Ecuador. After being forced to implement teleworking due to the COVID-19 pandemic, it decided to use this modality permanently despite the end of the health crisis. This work investigated how this modality affects the work environment, productivity, internal communication, motivation, sense of belonging, and mental health of employees. The analysis was carried out through surveys and interviews with 175 employees of the prepaid medical company, evaluating various aspects of teleworking. The results indicate that, although most employees accept teleworking as a favorable modality for their work area, there are concerns related to the effectiveness of communication, demand in job rotation, connection with the organizational culture, and the balance between personal and work life. Likewise, challenges such as distractions at home, job burnout, and difficulties in adapting to new technologies by adults were identified. Based on these findings, strategies are suggested to improve the organizational climate and mitigate the negative impacts of teleworking, focusing on strengthening communication, providing adequate technological support, and fostering a sense of belonging among employees.